Analisis kualitas pelayanan, harga dan lokasi dan kelengkapan produk yang mempegaruhi kepuasan konsumen toko kosmetik wardah (studi kasus pada mahasiswi Pondok Pesantren Luhur Wahid Hasyim Semarang - Chadhiq, Umar (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
This study aims to analyze the extent to which the influence of service quality, price, location and product completeness on customer satisfaction of wardah stores and to analyze the variables of service quality, price, location, and product completeness which most dominantly affect customer satisfaction. The research data were obtained from observations, interviews and questionnaires totaling 100 respondents based on the Slovin formula and using a Likert scale as the assessment. The analysis method uses multiple linear regression statistics and is processed using SPSS 16. The results of this study show that simultaneously service quality, price, location and product completeness have a positive and significant impact on customer satisfaction. Partially, price and product completeness have a positive and significant effect, while service quality has no positive and insignificant effect on customer satisfaction. And from the results of the regression coefficient, it can be seen that the most dominant variable affecting customer satisfaction is product completeness. This is because services have the largest beta value when compared to the variables of service quality and price Keywords: Service Quality, Price, location, Product Completeness, Satisfaction